Pengaruh Kondisi Keuangan Terhadap Kepatuhan Wajib Pajak Badan dalam Membayar Pajak (Studi Kasus Pada KPP Medan Barat) - Siregar, Siti Aisyah (Bursa : Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of financial conditions on corporate taxpayer compliance in paying taxes at KPP Pratama Medan Barat from 2018-2020. The type of research used in this research is associative research. The population in this study were all corporate taxpayers who were registered with KPP Pratama Medan Barat and 99 business entities were sampled. Data collection techniques using Simple Linear Regression testing. The research results obtained indicate that financial condition has a positive and significant effect on corporate taxpayer compliance.